2013
DOI: 10.1371/journal.pone.0070138
|View full text |Cite
|
Sign up to set email alerts
|

Applying Reversible Mutations of Nodulation and Nitrogen-Fixation Genes to Study Social Cheating in Rhizobium etli-Legume Interaction

Abstract: Mutualisms are common in nature, though these symbioses can be quite permeable to cheaters in situations where one individual parasitizes the other by discontinuing cooperation yet still exploits the benefits of the partnership. In the Rhizobium-legume system, there are two separate contexts, namely nodulation and nitrogen fixation processes, by which resident Rhizobium individuals can benefit by cheating. Here, we constructed reversible and irreversible mutations in key nodulation and nitrogen-fixation pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
(33 reference statements)
2
7
0
2
Order By: Relevance
“…On the other hand, and using an experimental method avoiding potentially confounding effects like the Ar: O 2 treatment, our present results are in agreement with our previous finding of no sanctions towards a cheating B. japonicum strain in the soybean split-root experiment mentioned earlier [26]. Other recent works on legume-rhizobia mutualisms using co-inoculated plants are given evidence that plants do not sanction cheating strains (in determinate nodules: Medicago truncatula-Sinorhizobium meliloti system: Gubry et al [31]; Phaseolus vulgaris-Rhizobium etli system: Ling et al [32]; in indeterminate nodules: M. truncatula and S. meliloti system: Heath and Tiffin [33]. On the other hand, works from Sachs et al [34] and Regus et al [35] on plants of Lotus strigosus (determinate nodules) co-inoculated with Bradyrhizobium strains with different fixation abilities, reported plant-host sanctions on the inefficient strains.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, and using an experimental method avoiding potentially confounding effects like the Ar: O 2 treatment, our present results are in agreement with our previous finding of no sanctions towards a cheating B. japonicum strain in the soybean split-root experiment mentioned earlier [26]. Other recent works on legume-rhizobia mutualisms using co-inoculated plants are given evidence that plants do not sanction cheating strains (in determinate nodules: Medicago truncatula-Sinorhizobium meliloti system: Gubry et al [31]; Phaseolus vulgaris-Rhizobium etli system: Ling et al [32]; in indeterminate nodules: M. truncatula and S. meliloti system: Heath and Tiffin [33]. On the other hand, works from Sachs et al [34] and Regus et al [35] on plants of Lotus strigosus (determinate nodules) co-inoculated with Bradyrhizobium strains with different fixation abilities, reported plant-host sanctions on the inefficient strains.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, there is only one published work with experimental conditions comparable to our present work, i.e., specifically testing plant-host sanctions in plants with determinate nodules and co-inoculating strains with equivalent nodulation rates but differing in fixation ability. Ling et al [32] constructed Rhizobium etli mutants in nifA genes responsible for nitrogen fixation and coinoculated plants of Phaseolus vulgaris (determinate nodules) with these deficient mutants and a normally fixing wild type strain. Ling et al [32] found a high number of cooccupied nodules and thus were able to confidently calculate the CFU number of nifA mutant and wild type strain in those nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Some prokaryotic microorganisms or soil bacteria have developed a unique biochemical mechanism that allow them to reduce N 2 to ammonia. Many of these microorganisms are able to associate symbiotically with other organisms, but leguminous is the only group of higher plants that have developed a wide symbiotic association (Fabra et al 2010;Ling et al 2013). The direct uptake of ammonium from the soil by the roots, as final product of nitrate assimilation or nitrogenase activity, is rapidly assimilated by the GS/GOGAT cycle, glutamine synthetase (GS, EC 6.3.1.2), glutamine oxoglutarate aminotransferase or simply glutamate synthase (GOGAT, EC 1.4.7.1) .…”
Section: Introductionmentioning
confidence: 99%
“…Alguns destes organismos (Rhizobium) têm a capacidade de associarem-se às raízes de leguminosas, formando nódulos ixadores de N 2 (LING et al, 2013).…”
Section: Introductionunclassified
“…De acordo com revisão realizada por Liu et al (2011), a presença de N mineral na rizosfera reduz a nodulação, o estabelecimento do nódulo e a atividade da enzima nitrogenase. Os danos ao aparato de ixação dependem da concentração de N no solo e, aparentemente, concentrações menores do que 2 mM de N combinado parecem não prejudicar as taxas de FBN.…”
Section: Introductionunclassified